2014
DOI: 10.3171/2014.6.peds13636
|View full text |Cite
|
Sign up to set email alerts
|

Ogilvie's syndrome after pediatric spinal deformity surgery: successful treatment with neostigmine

Abstract: Ogilvie's syndrome is a rare and potentially fatal disease that can easily be mistaken for postoperative ileus. Also known as acute colonic pseudo-obstruction, early recognition and diagnosis of the syndrome allows for treatment prior to bowel perforation and requisite abdominal surgery. The authors report a case of Ogilvie's syndrome following spinal deformity correction and tethered cord release in an adolescent who presented with acute abdominal distension, nausea, and vomiting on postoperative Day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…It occurs primarily in adult patients, whereas it happens rarely in children. It has been suggested that it could be the result of suppression of sacral parasympathetic nerves’ activity together with an increase in sympathetic impulses, resulting in inhibition of colonic motility and hence in colonic dilatation [5, 6, 10]. Other pathogenetic theories include prostaglandin E abnormalities, decreased splanchnic perfusion, side effects of neurotropic medications, metabolic disorders affecting neuromuscular conduction (hypokalaemia, uremia) and herpes zoster virus reactivation [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It occurs primarily in adult patients, whereas it happens rarely in children. It has been suggested that it could be the result of suppression of sacral parasympathetic nerves’ activity together with an increase in sympathetic impulses, resulting in inhibition of colonic motility and hence in colonic dilatation [5, 6, 10]. Other pathogenetic theories include prostaglandin E abnormalities, decreased splanchnic perfusion, side effects of neurotropic medications, metabolic disorders affecting neuromuscular conduction (hypokalaemia, uremia) and herpes zoster virus reactivation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Other pathogenetic theories include prostaglandin E abnormalities, decreased splanchnic perfusion, side effects of neurotropic medications, metabolic disorders affecting neuromuscular conduction (hypokalaemia, uremia) and herpes zoster virus reactivation [10]. Patients present with recurrent vomiting, nausea, abdominal pain and prominent abdominal distension [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The colonic dilatation, which is accompanied by intermittent flatus change and lack of bowel sounds, is relieved by colonoscopic decompression, water soluble contrast administered orally or rectally, naso-gastric aspiration, enema, neostigmine, or operation. Ogilvie's syndrome was described following spinal deformity correction and tethered cord release in an adolescent who presented with acute abdominal distension, nausea, and vomiting on postoperative first day [18]. This case is the first reported instance of neostigmine use for Ogilvie's syndrome treatment following a pediatric neurosurgical operation.…”
mentioning
confidence: 88%
“…OS is clinically diagnosed as diminished gastric motility that does not resolve on its own in a matter of days. Radiographically it is characterized by dilatation of cecum greater than 9 cm and lack of mechanical obstruction on abdominal CT. Neostigmine, a acetylcholinesterase inhibitor, is rarely used in treating OS if more conservative measures fail (40,42).…”
Section: Colonic Pseudo-obstruction and Bowel Perforationmentioning
confidence: 99%